Studi Implementasi Kebijakan Work From Home pada Pustakawan di LIPI - Noorika Retno Widuri (Perpustakaan Nasional, 2020)
Corona Virus Disease 2019 (COVID-19) pandemic that hits Indonesia makes leading Indonesian government take policy measures by launching regulations in implementation procedures within government agencies. LIPI issued a circular to promote Increasing Awareness and Prevention of Spreading of COVID-19 Infection within LIPI’s offices environment. The LIPI Scientific Documentation and Data Center (PDDI) received this mandate to carry out and regulate the policy for carrying out official duties at home (WFH). This paper aims to describe the implementation of the policy of carrying out official duties at home (WFH) for librarians in the PDDI LIPI. Implementation of this policy shows that as an implementing institution unit, PDDI follows up on the policy by issuing work from home assignments with provisions that refer to the circular of the head of LIPI. The target group in this policy is librarians in LIPI. This paper applies descriptive writing with quantitative data approach. The results of this study indicate that principally, the objectives of this policy have been achieved. The target group optimally carries out official duties at home. The survei shows that the target group has implemented the policy in accordance with the direction of LIPI Chairman. The communication pattern and interaction between the policy implementer and the elements implementing the policy are relatively good, so that the policy can be implemented as expected. Communication media is very flexible and not rigid, information related to policies, policy changes are conveyed through the WhatsApp group communication channel so that librarians can immediately receive the policy information. In this policy implementation model, the implementing organization minimizes the factors that make this policy not properly implemented, namely by arranging picket schedules, providing official vehicles for those who do not have private vehicles and lending work facilities to be brought home.